PENERAPAN MEDIA KOTAK WAYANG BERMUATAN WAWASAN KEINDONEESIAAN PADA KETERAMPILAN BERBICARA BIPA 3 - Nabilah, Hasna (Journal Educational of Indonesia Language, 2023)
Indonesian for Foreign Speakers (BIPA) is a program for foreign speakers to learn Indonesian as their second language. This study has a purpose, namely to describe the application of the wayang box media with material containing Indonesian insights on speaking skills in BIPA B1 learning. This study used descriptive qualitative method. This research was conducted through the BIPA learning process at level 3, where the research subjects were 3 foreign students, namely, two students from Thailand, and 1 person from Turkey with the same semester level, namely semester 6. Sources of data used in this study which is obtained from the results of the students' speaking skills using several techniques, including data collection techniques in the form of observing, taking notes, and giving oral tests, then drawing conclusions. The results of the study on BIPA level B1 learning on students' speaking skills, showed that the wayang box media containing Indonesian insights greatly affected the speaking skills of students, namely foreign students in BIPA learning. In addition, the wayang box media is very effectively used by BIPA teachers to achieve students' speaking skills.  Keywords: Puppet Box, Learning Media, Bipa.